POLÍTICAS PÚBLICAS E TUTELA COLETIVA: O CASO DE FALTA DE VAGAS EM CRECHES E PRÉ-ESCOLAS NO MUNICÍPIO DO RIO DE JANEIRO - Sara do Nascimento (TRF2, 2018)
Thisarticle analyzes the problem of lack of vacancies in kindergartens and pre-schools in the city of Rio de Janeiro, Brazil, focusing on the phenomenon of judicialisation of public policies in the Brazilian state. The judicial control of public policies has suffered severe criticism, such as: representing a usurpation of competences, facing the constitutional principles of separation, attacking the autonomy and independence of Legislative and Executive, as well as the principles of proportionality and reasonableness. Nonetheless, the non-compliance with public policies defined in the Constitution is a validating hypothesis of judicial intervention. The judicial control of these policies is based on the system of checks and balances, exercised by the Judiciary on the Executive and Legislative.